A Study on the impact of climatic changes in the coastal regions of Karnataka - Vinod G, Sushmitha G S (International Journal of Advanced Science and Technology, 2020)
A study on the effect of climatic changes in the coastal regions of Karnataka was carried out for Dakshina Kannada and Udupi districts being the study area. The objective of the study was to check the impact of climatic changes on the rainfall, temperature and relative humidity. Coefficient of determination (R2) was calculated on the basis of scatter plots which were plotted to compare the relationship between the three parameters i.e. Average Rainfall, Average Temperature and Average Relative Humidity. Results concluded that the average rainfall decreased between 2009 to 2017, and average temperature showed a gradual increase. However, the average Relative Humidity almost remained the same. The change analysis of land use land cover spanning over a period of eight years was calculated which showed an increasing trend in built up areas in urban as well as in rural areas, there was a significant decrease in forest cover (evergreen & deciduous). Decreasing trend in agricultural land usage and decrease in water bodies were also recorded to some extent.